BITS of success : inspiring stories of BITS Pilani alumni - Bhargava, Harsh; Murthy, Kinnera; Khendry, Anu (NEW DELHI: Universities Press, 2014)
the creators of hotmail, food king, Bharat forge, map My India, onida, the find, Marshall and the Buddh international circuit, to name a few, were all driven by passion(3z(Bthe passion to realise their dreams. They all built successful teams and created enduring brands. Further, the founders of the Companies all had one more thing in commodities graduated from bits pilani. These bits alumni and many more have been successful entrepreneurs and trailblazers in varied fields. How did they do it? Did they score a bullseye the first time? If not, did they experience frustration(3z(Blike many of us? How did they balance their work and personal lives? Did they have a success mantra? < br style="text-align: justify; the book provides answers to the above questions by taking the reader through the journeys of fifty individuals who realised their dreams through perseverance and determination, be it as entrepreneurs, technologists, scientists, teachers or artists. What is noteworthy is that all of them unanimously attribute their success to the exposure they received in bits pilani, highlighting the importance of Educational institutes in shaping students'' Lives. < br style="text-align: justify; this book is an initiative of bits alumni association, Hyderabad, to commemorate the Golden jubilee of bits pilanis
Includes index.
Keywords: Businesspeople -- India -- Biography; Success in business -- India